Behavioural activation versus guided self-help for depression in adults with learning disabilities: the BeatIt RCT. - Jahoda, Andrew (Health Technol Assess, 2018)
BACKGROUND: Depression is the most prevalent mental health problem among people with learning disabilities. OBJECTIVE: The trial investigated the clinical effectiveness and cost-effectiveness of behavioural activation for depression experienced by people with mild to moderate learning disabilities. The intervention was compared with a guided self-help intervention. DESIGN: A multicentre, single-blind, randomised controlled trial, with follow-up at 4, 8 and 12 months post randomisation. There was a nested qualitative study. SETTING: Participants were recruited from community learning disability teams and services and from Improving Access to Psychological Therapies services in Scotland, England and Wales. PARTICIPANTS: Participants were aged ≥ 18 years, with clinically significant depression, assessed using the Diagnostic Criteria for Psychiatric Disorders for use with Adults with Learning Disabilities. Participants had to be able to give informed consent and a supporter could accompany them to therapy. INTERVENTIONS: BeatIt was a manualised behavioural activation intervention, adapted for people with learning disabilities and depression. StepUp was an adapted guided self-help intervention. MAIN OUTCOME MEASURES: The primary outcome measure was the Glasgow Depression Scale for people with a Learning Disability (GDS-LD). Secondary outcomes included carer ratings of depressive symptoms and aggressiveness, self-reporting of anxiety symptoms, social support, activity and adaptive behaviour, relationships, quality of life (QoL) and life events, and resource and medication use. RESULTS: There were 161 participants randomised (BeatIt, n = 84; StepUp, n = 77). Participant retention was strong, with 141 completing the trial. Most completed therapy (BeatIt: 86%; StepUp: 82%). At baseline, 63% of BeatIt participants and 66% of StepUp participants were prescribed antidepressants. There was no statistically significant difference in GDS-LD scores between the StepUp (12.94 points) and BeatIt (11.91 points) groups at the 12-month primary outcome point. However, both groups improved during the trial. Other psychological and QoL outcomes followed a similar pattern. There were no treatment group differences, but there was improvement in both groups. There was no economic evidence suggesting that BeatIt may be more cost-effective than StepUp. However, treatment costs for both groups were approximately only 4-6.5% of the total support costs. Results of the qualitative research with participants, supporters and therapists were in concert with the quantitative findings. Both treatments were perceived as active interventions and were valued in terms of their structure, content and perceived impact. LIMITATIONS: A significant limitation was the absence of a treatment-as-usual (TAU) comparison. CONCLUSIONS: Primary and secondary outcomes, economic data and qualitative results all clearly demonstrate that there was no evidence for BeatIt being more effective than StepUp. FUTURE WORK: Comparisons against TAU are required to determine whether or not these interventions had any effect. TRIAL REGISTRATION: Current Controlled Trials ISRCTN09753005. FUNDING: This project was funded by the National Institute for Health Research Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 22, No. 53. See the NIHR Journals Library website for further project information.